Colliding drops as coalescing and fragmenting liquid springs. (3rd February 2017) - Planchette, C.; Hinterbichler, H.; Liu, M.; Bothe, D.; Brenn, G.
Abstract : A universal modelling approach of drop fragmentation after head-on drop collisions is presented. In this approach, the colliding drops are seen as liquid springs that coalesce, compress and relax, leading the merged drop to break up if it reaches a critical aspect ratio. Combining energetic balance of the compression and relaxation phases with a Rayleigh-like criterion, we deduce the fragmentation threshold velocity for the collision of two and three drops of the same liquid and of two drops of immiscible liquids. Predictions and experimental results obtained for these three kinds of collisions using various liquids and drop sizes are found to be in good agreement over a wide domain whose boundaries are discussed.